THE HARMONY OF LITERARY TEXT AND LITERARY CONTENT - A. A. Qayumov (Modern American Journals, 2025)
This article explores the interrelation between literary text and literary content, their harmonious formation, and the significance of this process in literary analysis. Particular attention is given to the role of linguistic units, functional segments, structure, and literary codes in revealing the literary content. Furthermore, the internal layers of the text are analyzed through the lens of structuralist theories, particularly those of Roland Barthes.
Keywords: Roland Barthes, text, content, analysis, code, codified rule, narrator, reader, personal form, impersonal form, text, function.